Evaluation of the corrosion resistance of AISI 316 stainless steel filters - Barbosa,Luzinete Pereira (2005)
In this investigation, the corrosion resistance of AISI 316 SS filters prepared with powders in the size ranges 74-44 µm and 210-105 µm and compacted with pressures of 300 MPa and 400 MPa has been evaluated in naturally aerated 0.5 M H2SO4 solution at 25 °C. Weight loss of filters manufactured with compacting pressure of 400 MPa were significantly higher than that of filters compacted at 300 MPa. The filter compacted at 400 MPa had higher carbon and nitrogen contents compared to those compacted at 300 MPa. The former also had chromium rich precipitates and oxides in the grain boundaries. The pores in filters compacted at 400 MPa were smaller than in filters compacted at 300 MPa. Smaller pores favor the formation of concentration cells and consequently, increased crevice corrosion.